Temporal variability in the diversity and composition of stream bacterioplankton communities - Portillo, Maria C.; Anderson, Suzanne P.; Fierer, Noah (Environmental microbiology, 2012)
Summary Bacterioplankton in freshwater streams play a critical role in stream nutrient cycling. Despite their ecological importance, the temporal variability in the structure of stream bacterioplankton communities remains understudied. We investigated the composition and temporal variability of stream bacterial communities and the influence of physicochemical parameters on these communities. We used barcoded pyrosequencing to survey bacterial communities in 107 streamwater samples collected from four locations in the Colorado Rocky Mountains from September 2008 to November 2009. The four sampled locations harboured distinct communities yet, at each sampling location, there was pronounced temporal variability in both community composition and alpha diversity levels. These temporal shifts in bacterioplankton community structure were not seasonal; rather, their diversity and composition appeared to be driven by intermittent changes in various streamwater biogeochemical conditions. Bacterial communities varied independently of time, as indicated by the observation that communities in samples collected close together in time were no more similar than those collected months apart. The temporal turnover in community composition was higher than observed in most previously studied microbial, plant or animal communities, highlighting the importance of stochastic processes and disturbance events in structuring these communities over time. Detailed temporal sampling is important if the objective is to monitor microbial community dynamics in pulsed ecosystems like streams.